THE DISTINCTION BETWEEN BRICS AND G7 IN RESPONDING TO THE UKRAINE-RUSSIA CRISIS: G20 MULTILATERAL CRISIS? - Ica Cahayani; Ahmad Mujaddid Fachrurreza; Agata Nina Puspita (Global South Review, 2022)
Introduction/Main Objective: This research discusses the differences in BRICS and G7 responses to the Ukraine-Russia conflict, where these two groups consist of countries with different political interests. Following the results of the G7 and BRICS Summits, both responded differently to the Ukraine-Russia crisis. Background Problem: Differences in response are proposed because the G20 has the vision to achieve the resolution of policy issues on problems that hinder world economic growth, one of which is the food crisis caused by the Uraina-Russia conflict. The selection of the G7 and BRICS's different responses is the right strategy to determine how much potential the G20 has. It is difficult to achieve its goal of providing solutions for the world economy thanks to the structure of its members, who have diverse interests and responses to the Ukraine-Russia crisis. Novelty: This study uses interest-based theory to analyze the differences in the responses of the G7 and BRICS. This theory seeks to explain the formation of the G20's international regime by dismantling aspects of the fundamental interests behind the cognitive states that decided to establish the international regime of the G20. Method: The method used in this research is the discourse analysis method in a case set because this study wants to see changes in discourse related to the multilateral G20. Findings/Results: The complexity of trading, namely the BRICS and G7, with different responses and interests in responding to the Ukrainian crisis, can encourage a multilateralism crisis in the G20. The research results prove that the complexity of reporting generates different interests, so the response to the Ukrainian-Russian crisis tends to differ. Conclusion: The G20 has not been able to overcome the different interests of its members in solving the problem of the world food crisis because the discussion of the world food crisis is linked to the discussion of Ukrainian-Russian security politics.